A search for young stellar objects as possible counterparts of Fermi sources - Munar Adrover, P. (2011)
Massive protostars have associated bipolar outflows which can produce strong shocks when interact with the surrounding medium. Some theoretical models predict that, under some conditions, particle acceleration at relativistic velocities can occur leading to gamma ray emission. In order to identify young stellar objects (YSO) that might emit gamma rays, we have crossed the Fermi First Year Catalog with catalogs of known YSOs, obtaining a set of candidates by spatial correlation. We have conducted Monte Carlo simulations to find the probability of chance coincidence. Our results indicate that ∼ 70% of the candidates should be gamma-ray sources with a confidence of ∼ 5σ.